2023
DOI: 10.1186/s12916-023-03059-3
|View full text |Cite
|
Sign up to set email alerts
|

Small volume bone marrow aspirates with high progenitor cell concentrations maximize cell therapy dose manufacture and substantially reduce donor hemoglobin loss

Jeremy Epah,
Gabriele Spohn,
Kathrin Preiß
et al.

Abstract: Background Bone marrow (BM) transplantation is a life-saving therapy for hematological diseases, and the BM harbors also highly useful (progenitor) cell types for novel cell therapies manufacture. Yet, the BM collection technique is not standardized. Methods Benchmarking our collection efficiency to BM collections worldwide (N = 1248), we noted a great variability of total nucleated cell (TNC) yields in BM products (HPC-M) with superior performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…RBC lysis is a faster and more easily standardized technique which can isolate MSCs by using ammonium chloride to break down RBCs whilst not affecting the composition of stem cells [ 83 ]. From a patient standpoint, studies have shown that low-volume aspirates are associated with fewer complications, such as minimal hemoglobin loss [ 84 ]. Furthermore, this offers a more efficient methodology to generate more MSCs.…”
Section: Sources Of Stem Cell-derived Exosomes: Molecular Traits Func...mentioning
confidence: 99%
“…RBC lysis is a faster and more easily standardized technique which can isolate MSCs by using ammonium chloride to break down RBCs whilst not affecting the composition of stem cells [ 83 ]. From a patient standpoint, studies have shown that low-volume aspirates are associated with fewer complications, such as minimal hemoglobin loss [ 84 ]. Furthermore, this offers a more efficient methodology to generate more MSCs.…”
Section: Sources Of Stem Cell-derived Exosomes: Molecular Traits Func...mentioning
confidence: 99%